Theoretical principles of Raman spectroscopy - Cialla-May, Dana; Schmitt, Michael; Popp, Juergen (Physical Sciences Review, 2019)
This contribution reports on the theoretical foundations of Raman spectroscopy. Since the discovery of the Raman effect in 1928, Raman spectroscopy with its linear and nonlinear variants has established itself as a powerful analytical tool in almost all scientific fields (chemistry, physics, material sciences, pharmacy, biology, (bio)medicine, geology, mineralogy, environmental sciences, etc.). First, a short introduction to linear Raman spectroscopy is given, followed by two approaches to increase the intrinsically weak Raman signal, namely resonance Raman and surface enhanced Raman spectroscopy. The last part of this contribution briefly introduces nonlinear Raman processes observed using pulsed lasers as excitation sources.
CRIS-Team Scopus Importer:2023-04-20
Keywords: non-linear Raman spectroscopy; Raman scattering; resonance Raman spectroscopy; surface enhanced Raman spectroscopy